Proceedings of the First ACM Conference on Online Social Networks 2013
DOI: 10.1145/2512938.2512946
|View full text |Cite
|
Sign up to set email alerts
|

Social resilience in online communities

Abstract: We empirically analyze five online communities: Friendster, Livejournal, Facebook, Orkut, and Myspace, to study how social networks decline. We define social resilience as the ability of a community to withstand changes. We do not argue about the cause of such changes, but concentrate on their impact. Changes may cause users to leave, which may trigger further leaves of others who lost connection to their friends. This may lead to cascades of users leaving. A social network is said to be resilient if the size … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
123
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 47 publications
0
123
0
Order By: Relevance
“…Garcia et al [129] studied a series of SNSs to understand what helps them survive, and when they become vulnerable. Their sample included Friendster (http://www.…”
Section: The Web As Scale-free Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Garcia et al [129] studied a series of SNSs to understand what helps them survive, and when they become vulnerable. Their sample included Friendster (http://www.…”
Section: The Web As Scale-free Networkmentioning
confidence: 99%
“…Garcia et al [129] argued that the long-term health of any SNS depends on a cost-benefit analysis. If the costs of being a member outweigh the benefits for a long enough period of time, a person is likely to leave.…”
Section: The Web As Scale-free Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al (2013) studied the relationship between user arrival and departure on social networks with respect to network topology, and elaborated on the important role of active friends in social networks in departure decisions. In another study based on network topology, Garcia et al (2013) focused on understanding the resilience of social networks and how friends' departures impact focal users. Giliette (2011) provided a more popular view on some of the technical, managerial, financial, and social issues that could lead to social media outlet failure.…”
Section: Introductionmentioning
confidence: 99%
“…To identify social influence, traditional measures focused on the concept of centrality [12], often measuring it as degree or betweenness centrality [13]. Recent works have shown that coreness centrality [14,15] outperforms degree and betweenness centrality in detecting influentials both data-driven simulations [16] leading to applications to political movements [17,18], scientific rumors [19,20], gender inequality in Wikipedia [21], and cascades of users leaving a social network [22].…”
Section: Introductionmentioning
confidence: 99%